2009
DOI: 10.1021/jp902204a
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of the High-Temperature Oxidation of o-, m- and p-Xylyl Radicals

Abstract: Theoretical calculations at the CBS-QB3 level of theory have been performed to investigate the potential energy surface for the reaction of o-, m- and p-xylyl with molecular oxygen. The differences of the relative potential energies for the products and the transition states of o-, m- and p-xylyl with molecular oxygen were found to be within 8.5 kJ/mol at the CBS-QB3 level of theory. Although the reaction of m- and p-xylyl radicals with molecular oxygen have the same reaction pathways and also the same reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In daytime, the reaction of aromatic hydrocarbons with hydroxyl radicals is the major atmospheric loss process [14][15][16]. Several previous experimental [17][18][19] and theoretical [20][21][22][23][24][25][26] studies have unraveled the elementary reactions involved in aromatic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In daytime, the reaction of aromatic hydrocarbons with hydroxyl radicals is the major atmospheric loss process [14][15][16]. Several previous experimental [17][18][19] and theoretical [20][21][22][23][24][25][26] studies have unraveled the elementary reactions involved in aromatic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…As described in our recent n-propylbenzene paper [44], the addition reactions of the benzyl radical to molecular oxygen, an important step in the low temperature mechanisms of alkylbenzenes in general, have been derived by fitting over the temperature range of interest (600-900 K) the reaction rates that have been theoretically calculated by Murakami et al [46] for the xylyl + O 2 system. The reaction rate for the concerted elimination of HȮ 2 radical from the alkylperoxy species have been derived from Altarawneh et al [47], as in [44].…”
mentioning
confidence: 99%
“…Figure 5 summarizes the calculated optimized geometries of these structures at the B3LYP/6-311G(2d, d, p) level of theory. It was revealed that the transition state structure TS6a for the dissociation of the cyclic O 2 intermediates 5a resembled with that for the concerted dissociation of the cyclic O 2 intermediate of the benzylperoxy radicals [16] as well as that of o-xylylperoxy radicals [5]. Table II Table II are also summarized in Figure 6.…”
Section: Subsequent Reactions Of the Cyclic O 2 Intermediates From Thmentioning
confidence: 82%
“…As there were no distinct transition states for such backward reactions, variable transition state for each temperature was determined by searching the geometries that give maximum Gibbs free energies at each temperature. Because the DFT was one of the most accurate and relatively low-cost level of theories that could predict the accurate potential energy profiles of benzyl þ O 2 [16] and xylyl þ O 2 [5] reaction systems, and furthermore Senosiain et al [21] and Silva et al [22] also succeeded in calculating the minimum energy profiles for the OH þ acetylene reaction and for the thermal decomposition of benzyl radical using the B3LYP method, respectively, we have applied the same theory to determine the variable transition state for the backward reactions of the phenylethylperoxy radicals to form phenylethyl þ O 2 . Figure 7 shows the potential energy profiles for the backward dissociation pathways of a-phenylethyl (C 6 H 5 CHCH 3 O 2 , 1a) þ O 2 and b-phenylethyl (C 6 H 5 CH 2 CH 2 O 2 , 1b) þ O 2 .…”
Section: High-pressure Limit Rate-con-stants For the Primary And Subsmentioning
confidence: 99%
See 1 more Smart Citation